An overview of Eagle's syndrome. Issue 4 (November 2021) - Searle, Emma; Searle, Adrian
Eagle's syndrome is a condition that typically does not present to pain clinics. It consists of an elongated styloid process greater than 25 mm and/or stylohyoid ligament calcification causing an unusual array of symptoms, relating to anatomical involvement. Multiple specialities may be involved with the diagnosis of this rare condition. Three-dimensional reconstructive computed tomographic (CT) scan remains the gold standard for diagnosis. Depending on the presenting symptoms, care should be directed to an appropriate specialist. Pain surrounding Eagle's syndrome does not typically resolve using simple pharmacological methods. Eagle's syndrome should remain a diagnosis to be considered when faced with non-resolving head/facial pain.